2012
DOI: 10.1136/jclinpath-2012-200901
|View full text |Cite
|
Sign up to set email alerts
|

Faecal markers of gastrointestinal inflammation

Abstract: Gastrointestinal (GI) symptoms including abdominal pain, bloating and diarrhoea are a relatively common reason for consulting a physician. They may be due to inflammatory bowel disease (inflammatory bowel disease; Crohn's disease, ulcerative colitis and indeterminate colitis), malignancy (colorectal cancer), infectious colitis or irritable bowel syndrome (IBS). Differentiation between these involves the use of clinical, radiological, endoscopic and serological techniques, which are invasive or involve exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 46 publications
1
61
0
11
Order By: Relevance
“…73 Lactoferrin is an iron-binding protein present in neutrophils. 188 Faecal lactoferrin (FL) is stable at room temperature for 4 days. 189 There are suggestions that FL is as good as FC for differentiating IBD from non-IBD.…”
Section: Lactoferrinmentioning
confidence: 99%
See 1 more Smart Citation
“…73 Lactoferrin is an iron-binding protein present in neutrophils. 188 Faecal lactoferrin (FL) is stable at room temperature for 4 days. 189 There are suggestions that FL is as good as FC for differentiating IBD from non-IBD.…”
Section: Lactoferrinmentioning
confidence: 99%
“…189 For differentiating IBD from IBS, the sensitivity of lactoferrin ranged between 78% and 82%, whereas the specificity ranged between 85% and 100% in studies. 188 Schoepfer et al 75 compared the accuracy of faecal markers, blood leucocytes, CRP and IBD antibodies in discriminating IBD from IBS and found that the overall accuracies of FC ELISA (PhiCal test -89%) and lactoferrin (IBD-SCAN -90%) were similar. In another study 190 using colonoscopy as the reference standard, the sensitivity, specificity, PPV and diagnostic efficacy were slightly higher with lactoferrin (80%, 85%, 87% and 81%, respectively) than with calprotectin (78%, 83%, 86% and 80%).…”
Section: Lactoferrinmentioning
confidence: 99%
“…Calprotectin, a 36.5 kDa hetero-trimer, consisting of one S100A8 light chain and two S100A9 heavy chains belonging to the S100 calcium binding proteins family, is present in the cytoplasm of granulocytes and accounts for about 60% of soluble proteins; it is secreted extracellularly from stimulated neutrophils and monocytes or released by cell disruption or death [44]. Both lactoferrin and calprotectin have antimicrobial properties: histidine-based zinc-binding sequences (His-X-X-X-His motif) are involved in the antimicrobial activity of calprotectin, while the amino-terminal domain (lactoferricin) liberated by pepsin Røseth et al [47] CD and UC 77%/100% Solem et al [48] CD 54%/75% D'Incà et al [49] CD 77%/80% 81%/80% D'Incà et al [49] UC 75%/60% 78%/70% Sipponen et al [50] CD 77%/100% 87%/100% Schoepfer et al [51] UC 86%-93%/71%-88% Schoepfer et al [52] CD 89%/58% 68%/58% Sipponen et al [53] CD 80%/67% 80%/89% Lobatòn et al [54] UC 74%/90% 84%/38%…”
Section: Lactoferrin and Calprotectin: Biochemical Properties Pre-anmentioning
confidence: 99%
“…These findings suggest that each laboratory should investigate the transferability of published and/or manufacturers' cut-off values not only to its own patients' population but also to its own pre-analytical procedures for sample preparation. The upper normal limits for both calprotectin and lactoferrin, which have mainly been established by using manual processing of the stool samples, appear to be age-dependent: while for adults and adolescents it is estimated at 50 μg/g for calprotectin and 7-11 μg/g for lactoferrin [44,62], in children younger than 10 years, values three to four-fold the reference cut-off are suggested [63]. Likewise, a separate reference range two-fold higher than the reference cut-off is required in patients over 60 years of age [63].…”
Section: Lactoferrin and Calprotectin: Biochemical Properties Pre-anmentioning
confidence: 99%
“…Це обмежує його ви-користання в дітей, підлітків та жінок дітородного віку. Також не можна не враховувати високу вартість самих радіонуклідів, що в результаті робить метод економіч-но невигідним -близько 300 фунтів на одного пацієн-та [32,35].…”
unclassified